Analysis of Uromodulin Polymerization Provides New Insights into the Mechanisms Regulating ZP Domain-mediated Protein Assembly - Céline Schaeffer; S Santambrogio; Simone Perucca; Giorgio Casari; Luca Rampoldi (2008)
Uromodulin is the most abundant protein secreted in urine, in which it is found as a high-molecular-weight polymer. Polymerization occurs via its zona pellucida (ZP) domain, a conserved module shared by many extracellular eukaryotic proteins that are able to assemble into matrices. In this work, we identified two motifs in uromodulin, mapping in the linker region of the ZP domain and in between protein cleavage and glycosylphosphatidylinositol (GPI)-anchoring sites, which regulate its polymerization. Indeed, mutations in either module led to premature intracellular polymerization of a soluble uromodulin isoform, demonstrating the inhibitory role of these motifs for ZP domain-mediated protein assembly. Proteolytic cleavage separating the external motif from the mature monomer is necessary to release the inhibitory function and allow protein polymerization. Moreover, we report absent or abnormal assembly into filaments of GPI-anchored uromodulin mutated in either the internal or the external motif. This effect is due to altered processing on the plasma membrane, demonstrating that the presence of the two modules has not only an inhibitory function but also can positively regulate protein polymerization. Our data expand previous knowledge on the control of ZP domain function and suggest a common mechanism regulating polymerization of ZP domain proteins.